Media Promosi Kesehatan Hygiene Sanitasi Pengolahan Makanan pada Industri Rumah Tangga Tempe - Dimas Yoga Saputra; Hanifa Maher Denny; Yuliani Setyaningsih (Politeknik Kesehatan Tanjung Karang, 2021)
The majority of the people of Beji Village, Batu City, make a living as tempe craftsmen. Observations related to the sanitation hygiene of tempe processing workers are still not good. Based on the results of interviews with the head of the tempe craftsmen association in Beji Village, it is stated that there has never been any counseling related to sanitation hygiene. For this reason, promotion efforts are needed. food processing hygiene and sanitation to increase knowledge of personal hygiene attitudes and practices at work. This study uses the Research and Development (R&D) design and the P-Process theoretical framework, namely from step 1 in the form of target analysis, step 2 strategic design, to step 3 media development. Questionnaires were given to 20 respondents and interviewed to explore the characteristics of respondents. In addition, validation tests were also carried out by 4 expert reviewers. Tempe home industry workers need additional information about personal hygiene standards and behavior at work. The media created were adapted to the characteristics of the respondents using Indonesian and the Malangan local language as slogans. The results of this study were posters, leaflets, and videos with messages about the importance of personal hygiene in working using a rational approach with the aim that the target gains new knowledge to increase knowledge Attitudes and practices of processing workers are related to the importance of personal hygiene at work.